Gender wage differential in the labour market of Bhutan (2009-2022) - Yuden, Phuentsho (International Journal of Publication and Social Studies, 2023)
This study investigated striking gender wage differentials trend in Bhutan between 2009 and 2022. In order to decompose the gender wage differentials, we used household level micro-data of Labor Force Survey (LFS), which was conducted by then Ministry of Labor and Human Resources (MoLHR) and National Statistics Bureau (NSB). The methodology estimates the sources of gender wage differentials by segregating gender-specific factors and general wage structure factors. The explanatory variables like women’s labor market skills (education, work experience) and women’s choice into certain occupational and industrial groups; and treatment towards women employees by employers (i.e., discrimination) are categorized into gender-specific factors. Whereas, the sum of observed prices of labor market skills (education and work experience) and price of women’s segregation into certain occupational and industrial groups and unobserved prices were termed wage structure factors. The result shows that gap in education and women’s choice into low paying jobs increased gender wage differentials. However, increase in women’s work experience narrowed the gender wage differential. Therefore, the widening gender wage differentials resulted from gender-specific factors by huge margin. The findings from this study will help decision and policy makers in developing policies which helps narrowing education and skills gaps between men and women. In addition, it will also help in drafting policies which helps women in getting better paying jobs.